Analysis of Trends in the Number of Teachers in India from 2001-2002 to 2022-2023: Insights and Implications for Education Policy (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper presents a comprehensive analysis of the number of teachers in India over the two-decade period from 2001-2002 to 2022-2023. It highlights significant growth trends, periods of stagnation and phases of decline and recovery in the education sector. The data indicates a significant increase in the number of teachers, starting at 426,797 in 2001-2002 and peaking at 1,642,524 in 2022-2023. Noteworthy is the highest growth rate of 63% observed in 2011-2012, followed by periods of stagnation and a notable decline in 2016-2017 with a growth rate of -10.1%. This study underscores the importance of consistent policy support and strategic investments to sustain the growth of teaching personnel, which is essential for the enhancement of educational outcomes.